Effect of Carrots (Daucus carota L.) on Gastric Histopathology of Piroxicam-Induced Mice as a Peptic Ulcer Prevention - Jennifer Susanto; Danti Nur Indiastuti; Gondo Mastutik (Faculty of Medicine Universitas Airlangga, 2022)
Highlights:1. Carrots (Daucus carota L.) can reduce the side effects of non-steroidal anti-inflammatory drugs (NSAIDs) due to its gastroprotective components.2. Histopathological studies of the gastric inflammation signs showed that carrots can prevent NSAID-induced peptic ulcers. AbstractIntroduction: Non-steroidal anti-inflammatory drugs (NSAIDs) consumption contributes significantly to gastrointestinal morbidity, including peptic ulcers. NSAIDs cause gastric mucosal damage by inhibiting PGE2 and PGI2 secretion, increasing HCl secretion, and also causing local irritation and neutrophil adhesion. Flavonoids and chlorogenic acid are gastroprotective agents found in carrots (Daucus carota L.). Therefore, this study aimed to validate the effect of carrots on gastric histopathology of piroxicam-induced mice.Methods: This was an experimental study using a post-test-only control group design. 35 mice were divided into 5 groups and were allowed to adapt for 1 week. The negative control group received 0.25 mL aqua dest, while the positive control group received 0.104 mg famotidine. Group A, B, and C received carrot extract with each dosage was 200 mg/kgBW, 300 mg/kgBW, and 400 mg/kgBW. The mice were induced 2 hours later with 0.052 mg piroxicam. The treatments lasted 14 days. Each stomach was taken and examined on the 15th day. Afterward, histopathological preparations were made.Results: The results of the histopathological signs of inflammation using the Kruskal-Wallis method showed p = 0.000, indicating that there was an effect of the carrot extract in preventing the inflammation on the gastric histopathology (p < 0.05).Conclusion: In conclusion, this study confirmed that carrot extract is more effective in avoiding peptic ulcers due to NSAID consumption.